(untitled) (International Journal of Built Environment and Sustainability, 2021)
Social cohesion in public open spaces has been recommended as one of the key elements for improving the wellbeing of the elderly. Social cohesion includes relational elements and individuals’ feeling of association. Over the past few decades, increasing social interaction in the neighbourhood is part of larger urban areas and has been regarded as one of the social sustainability initiatives and plays an important role in megacities sustainability. Comprehending place attachment is necessary to enhance elderly people’s interactions to make them self-reliant. The study aims to identify the characteristics of open spaces with their major influential factors for enhancing social cohesion for the well-being of the elderly in an urban residential environment through a systematic literature review. The study focuses on addressing three research questions and analysing its results from primary literature studies in the review process. Ten electronic databases were searched for relevant work from papers written in English between 2011 and 2021. Quantitative, qualitative, and mixed methods studies were included. A narrative synthesis was carried out of published works to address the research questions after identifying the various characteristics. The review, which includes 57 published papers, found that the Open spaces are ideally characterized by accessibility, walkability, reduced fear and security, built environment characteristics, landscape elements, climate, best practices, and New Urbanism principles. On the other hand, social cohesion is influenced by activities, safety and security, public places, accessibility, natural elements, noise levels, vehicular interruptions, dimensions and geometry, climate, and physical amenities. A conceptual framework relating to open space attributes and social cohesion is proposed as the finding of the research. Prioritizing the attributes based on the physical, behavioural, and psychological needs of the elderly to keep them active in their aging process could be the further scope of research in this direction.